Pediatric Patients with Intravascular Devices: Polymicrobial Bloodstream Infections and Risk Factors. (23rd March 2011) - Onland, Wes; Pajkrt, Dasja; Shin, Cathy; Fustar, Stana; Rushing, Teresa; Wong, Wing-Yen
Abstract : A retrospective study was conducted, including 61 patients with long-term intravascular devices (IVDs) admitted to the Childrens Hospital Los Angeles with diverse underlying diseases, different types of catheters, and culture-proven catheter-related bloodstream infections (BSIs). Within these patients, 125 catheter-related BSIs occurred, and the incidence of monomicrobial and polymicrobial BSIs was evaluated. Risk factors for polymicrobial BSIs were determined. Forty-two BSIs contained more than one pathogen. These polymicrobial BSIs were observed more often in younger patients (<4.1 years versus ≥4.1 years) and less in patients using venous implanted ports. No other associations were found between the occurrences of polymicrobial BSIs and underlying diseases, other types of catheters, host defense status, parenteral nutrition, recurrences, or catheter removal. Patients with long-term IVDs at a younger age have a higher risk of developing a polymicrobial BSI. Future prospective studies should address the issue of polymicrobial infection in IVDs in more detail.